2022
DOI: 10.1007/s10803-022-05440-2
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Interventions to Promote Health and Behavior-Related Outcomes in Adolescents with Autism Spectrum Disorder

Abstract: This systematic review examined the effectiveness in a hybrid telehealth model for adolescents with autism spectrum disorder (ASD), exploring the evidence base, methodology, and outcomes of health and behavior-related interventions for adolescents with ASD. The 11 included studies (a) were quantitative, (b) evaluated interventions delivered through a hybrid telehealth model (i.e., combined remote intervention with minimal in-person procedures), (c) measured health and behavior-related outcomes, and (d) conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…Recent research demonstrated the efficacy of telehealth-based occupational therapy services among various populations ( Little et al, 2021 ; Nissen & Serwe, 2018 ). Lamash et al (2022) conducted a systematic review to evaluate remote (including pre-pandemic) interventions promoting health-related outcomes for autistic AYA. Results indicated a lack of empirical evidence on their efficacy in promoting autonomous daily functioning and social participation and inadequate information on which autistic individuals might benefit most from directly delivered remote interventions ( Ellison et al, 2021 ; Ford et al, 2021 ).…”
mentioning
confidence: 99%
“…Recent research demonstrated the efficacy of telehealth-based occupational therapy services among various populations ( Little et al, 2021 ; Nissen & Serwe, 2018 ). Lamash et al (2022) conducted a systematic review to evaluate remote (including pre-pandemic) interventions promoting health-related outcomes for autistic AYA. Results indicated a lack of empirical evidence on their efficacy in promoting autonomous daily functioning and social participation and inadequate information on which autistic individuals might benefit most from directly delivered remote interventions ( Ellison et al, 2021 ; Ford et al, 2021 ).…”
mentioning
confidence: 99%
“…All participants in both programs reported that the virtual format was feasible and acceptable, as the virtual setting eliminated the need to travel to and from intervention sessions, providing more flexibility in their schedules for participation. It also allowed for participants to partake in the interventions in the familiarity of their homes, which may be considered as ideal in individuals with ASD who struggle with changes in activity or routine ( Lamash et al, 2022 ). Participants reported that there were adequate opportunities for interaction and engagement in both interventions through the usage of webcams, screen sharing, and chat.…”
Section: Discussionmentioning
confidence: 99%
“…levels of hyperactivity, oppositionality, intelligence, social communication impairment, and cognitive abilities), and according to ASD diagnostic status particularly as the non-ASD studies have not excluded on this basis - thus constraining comparisons with present findings. Indeed, a recent systematic review concluded that there is a need for more studies to explore the effectiveness of hybrid models for autistic individuals ( Lamash, Little, & Hen-Herbst, 2022 ).…”
Section: Discussionmentioning
confidence: 99%